Dental caries and associated factors among diabetic and nondiabetic adult patients attending Bichena Primary Hospital’s Outpatient Department - Shiferaw, Anley; Alem, Girma; Tsehay, Mekonnen; Kibret, Getiye Dejenu (Frontiers in Oral Health, 2022)
ABSTRACT Purpose: Dental caries is a significant public health issue affecting both diabetic and nondiabetic population. However, the problem and associated factors of dental caries among diabetics and nondiabetics patients is not well-known in Ethiopia. This study aims to compare the prevalence of dental caries and associated factors among diabetic and nondiabetic patients at Outpatient Department of Bichena Primary Hospital northwest, Ethiopia. Methods: This Institutional based, comparative cross-sectional study was conducted from October 7, 2019 to December 6, 2019 among 200 diabetes and 400 nondiabetic adult patients. A consecutive sampling technique was used to recruit study participants. The data were collected by a pretested structured questionnaire. The data were entered into Epi data version 3.1 and exported to SPSS version 20 for analysis. Bivariable and multivariable logistic regressions were employed. Variables were declared statistically significant when p-value <0.05. Results: A total of 582 patients were involved in the study with a response rate of 97.0%. The magnitude of dental caries in nondiabetic group were 67.90% (95%CI: 63.20-72.80%) and for diabetics 79.60 %( 95%CI: 74.0-85.70%). This prevalence shows significant difference between groups (chi-square=8.817: p-value=0.003). Females (AOR= 1.79, 95% CI: 1.15, 2.77), poor oral hygiene (AOR= 2.95, 95% CI: 1.71, 5.11), not cleaning teeth (AOR= 3.26, 95% CI: 2.13,4.97), felling dry mouth (AOR= 2.31, 95% CI: 1.11, 4.81), sugared-tea drinking (AOR= 2.00, 95% CI: 1.18, 3.38), Inadequate oral-health knowledge (AOR= 3.51, 95% CI: 2.19, 5.62), and khat chewing (AOR= 2.14, 95% CI: 1.24, 3.71) were significantly associated with high prevalence of dental caries. Conclusion: The magnitude of caries was significantly higher among diabetics than non-diabetics. Therefore, oral health education with preventive measures such as improving teeth cleaning practice, reducing intake of sugary foods and drinks, improving oral hygiene practice of patients must be done to control dental caries in the study area. Keywords: dental caries, diabetics, nondiabetics, patients, and Ethiopia.